Development of Mathematics Learning Tools Based on the Discovery Learning Model with the RME Approach Containing Mathematical Literacy - Amalia, Eka Nurul; Maharani, Rizqona (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2025)
Indonesian students' mathematical literacy skills were categorized as low based on the results of the 2022 PISA test. This can be improved by providing students with mathematical literacy-based learning. Previous studies have shown that the majority of educators are familiar with mathematical literacy, but are unable to design learning that includes mathematical literacy. Based on this condition, a mathematical literacy-based learning tool was developed to support the improvement of students' mathematical literacy skills. Three learning tools were developed: a teaching module, a worksheet, and summative mathematical literacy questions. These three learning tools were developed using the RND method and the 4D model. Based on validity testing by two experts using V-Aiken, the results were 0.97 for the teaching module, 0.93 for the worksheet, and 0.95 for the summative mathematical literacy test questions, all of which were declared very valid. Meanwhile, based on the practicality test, an average score of 95% was obtained for the teaching module, 95% for the student worksheet, and 94% for the summative mathematical literacy test questions. All three were declared highly practical. Because the learning tools have been declared highly valid and highly practical, the learning tools developed can be implemented in the learning process.